Mengajarkan Nilai-Nilai Islam pada Anak Melalui Kegiatan Mengaji dan Sosialisasi Pentingnya Menjaga Kebersihan pada Anak : Pengabdian - Rismawati; Rita; Hartanti; Ajeng Teni Nur Afriliani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of carrying out activities applied to the community is to provide an understanding of Islamic values through prayer to children and provide an understanding of the importance of dental hygiene in children and provide early detection measures for cavities. These activities will include observation methods, workshops, group work programs and evaluations. Behind the success of these activities, there are several supporting materials in carrying out these activities, namely the Qur'an, toothbrush and toothbrush teaching aids, as well as articles or journals in supporting the delivery of material about dental hygiene. The results of the activities have been achieved by forming the habit of maintaining dental hygiene for every day and the spirit of carrying out activities based on Islamic values. By doing this activity, children understand and gain knowledge about Islamic values and understand maintaining dental hygiene for every day. After carrying out the KKN work program to the community, the suggestions that we can give to the community to take better care of the heritage or attributes made during the KKN and the local government pays more attention to the condition of the family there, especially the children of the young generation of Indonesia..